Efficacy and Safety of TCMI in Patients With Combined Coronary Heart Disease and Heart Failure: A Systematic Review and Network Meta-Analysis - Penglu Wei; Kuo Yang; Dehuai Long; Yupei Tan; Wenlong Xing; Xiang Li; Hongli Wu; Hongxu Liu (Frontiers Media S.A., 2021)
Objective: To compare the efficacy and safety of conventional treatments (CTs) to those that included traditional Chinese medicine injections (TCMIs) in patients with combined coronary heart disease and heart failure (CHD-HF).Methods: Eight electronic literature databases (PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, China National Knowledge Infrastructure Database, Chinese Scientific Journal Database, Wanfang Database, Chinese Biomedical Database) were searched from their inceptions to May 18, 2021, to identify relevant randomised controlled trials (RCTs). The primary outcomes analyzed included the total effectiveness rate and adverse events (ADRs). The secondary outcomes analyzed included the left ventricular ejection fraction (LVEF), N-terminal pro-brain natriuretic peptide (NT-proBNP), brain natriuretic peptide (BNP), and 6-min walk test (6MWT). Cochrane risk-of-bias tool was used to assess quality of the analyzed RCTs. Stata and OpenBUGS software were used to prior to the systematic review and network meta-analysis.Results: Sixty-one eligible trials involved 5,567 patients and one of the following 15 TCMIs: Shuxuetong, Shenmai, Shenfu, Shengmai, Danshenduofenyansuan, Danhong, Dazhuhongjingtian, Xinmailong, Dengzhanxixin, Gualoupi, Shuxuening, Xuesaitong, Yiqi Fumai, Shenqi Fuzheng, Huangqi. Network meta-analysis revealed that Shuxuetong injection + CT group was superior to CT only in improving the total effectiveness rate [odds ratio (OR): 7.8, 95% confidence interval (CI): 1.17-27.41]. Shenmai injection + CT was superior to CT only for LVEF (OR: 8.97, CI: 4.67-13.18), Xinmailong injection + CT was superior to CT only for NT-proBNP (OR: −317.70, CI: −331.10-303.10), Shenqi Fuzheng injection + CT was superior to CT only for BNP (OR: −257.30, CI: −308.40-242.80); and Danhong injection + CT was superior to CT only for 6MWT (OR: 84.40, CI: 62.62−106.20). Different TCMIs had different toxicity spectrums.Conclusion: TCMIs combined with CT are better than CT alone in treating CHD-HF. Different TCMIs improve different outcomes. Additional properly designed RCTs are needed to conduce a more refined comparison of various TCMIs.Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42021258263].